Islam in The Modern World: Tradition, Revolution and Culture. Volume 2 - HANAFI, Hassan (Dar Kebaa Bookshop, 2000)
Islam in The Modern World: Tradition, Revolution and Culture. Volume 2 Dunia Islam Budaya Islam Islam Dunia MOdern Tradisi Islam Revolusi Dalam ISlam